Stress among Health Professionals - García-Moran, María de Carmen (2016)
Stress among health professionals constitutes a significant problem, because of its strong impact both on them and their patients. This study finds that this syndrome varies according to gender, type of work and job role. We find that primary, secondary and tertiary prevention strategies are effective in minimizing this syndrome. These include better work management, an adjusted work schedule, a balance between work and family life, workforce personnel involvement, and improvement of employment policies which emphasize health promotion.